Religious Pluralism in Indonesia : Threats and Opportunities for Democracy - Formichi, Chiara, 1982- (Book collections on Project MUSE., 2021)
"Addresses the state of religious pluralism in the post-Suharto era (1965-1998) with case-studies from across the religious spectrum (Animism, Buddhism, Christianity, Confucianism, Hinduism, and Islam) and across the social sciences. The volume opens a number of windows on how the state, its government bodies, civil society groups, and individuals have experienced the five principles of Pancasila as a framework for the attempted integration of minorities and majorities across the archipelagic state"--